Demand for malaria rapid diagnostic test, health care-seeking behaviour, and drug use among rural community members with fever or malaria-like illness in Ebonyi state, Nigeria: a cross-sectional household survey - Ugwu I. Omale; Onyinyechukwu U. Oka; Ifeyinwa M. Okeke; Benedict N. Azuogu; Chihurumnanya Alo; Ugochukwu C. Madubueze; Irene I. Eze; Kingsley C. Okeke; Rowland Utulu; Uduak E. Akpan; Chijioke V. Iloke; Anthonia O. Nnubia; et al. (BMC, 2021)
Abstract Background A good understanding of the demand for malaria rapid diagnostic test (MRDT), malaria health care-seeking behavior, and drug use among community members is crucial to malaria control efforts. The aim of this study was to assess the demand (use and/or request) for MRDT, health care-seeking behavior, and drug use, as well as associated factors, among rural community members (both children and adults) with fever or malaria-like illness in Ebonyi state, Nigeria. Methods A cross-sectional household survey was conducted between October 1st and November 7th, 2018, in 18 rural geographical clusters. Data was collected using a structured interviewer-administered questionnaire. Descriptive analysis was done using summary statistics. Associated factors (socio-demographic, knowledge and opinion level) were assessed using bivariate and multivariate binomial logistic regressions while the overall effects of these factors were assessed using the "postestimation test" command in Stata. Results A total of 1310 children under 5 years of age and 2329 children ages 5 years and above and adults (excluding pregnant women) (3639 overall) participated in the study. Among the 1310 children under 5 years of age: 521 (39.8%) received MRDT of which the caregivers of 82 (15.7%) requested for the MRDT; 931 (71.1%) sought care with public/private sector providers (excluding traditional practitioners/drug hawkers) the same/next day; 495 (37.8%) sought care at government primary health centres, 744 (56.8%) sought care with the patent medicine vendors (PMVs); 136 (10.4%) sought care with traditional practitioners; 1020 (77.9%) took ACTs (=88.2%, 1020/1156 of those who took anti-malarial drugs). Generally, lower values were respectively recorded among the 2329 children ages 5 years and above and adults (excluding pregnant women). The most important overarching predictor of the demand for MRDT and care-seeking behaviour was the knowledge and opinion level of respondent female heads of households about malaria and malaria diagnosis. Conclusions Among the rural community members with fever or malaria-like illness in Ebonyi state, Nigeria, while majority did not receive MRDT or diagnostic testing, and sought care with the PMVs, most took anti-malaria drugs, and mostly ACTs. Interventions are needed to improve the knowledge and opinion of the female heads of households about malaria and malaria diagnosis.